2018
DOI: 10.1016/j.bbmt.2018.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Cohort-Controlled Comparison of Umbilical Cord Blood Transplantation Using Carlecortemcel-L, a Single Progenitor–Enriched Cord Blood, to Double Cord Blood Unit Transplantation

Abstract: Umbilical cord blood (UCB) transplantation has a high early mortality rate primarily related to transplanted stem cell dose. To decrease early mortality and enhance engraftment, a portion of selected cord blood units (20% to 50%) was expanded with cytokines and the copper chelator tetraethylenepentamine (carlecortemcel-L) and transplanted with the unmanipulated fraction after myeloablative conditioning. The primary endpoint was 100-day survival, which was compared with a contemporaneous double-unit cord blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Acute and chronic graft-versus-host disease rates were similar. The study suggests that transplanting expanded CD34+ stem cells from a portion of single UCB unit along with unmanipulated portion improved 100-day survival while improving neutrophil and platelet engraftments [16].…”
Section: Stemex® Copper Chelator Expansionmentioning
confidence: 90%
“…Acute and chronic graft-versus-host disease rates were similar. The study suggests that transplanting expanded CD34+ stem cells from a portion of single UCB unit along with unmanipulated portion improved 100-day survival while improving neutrophil and platelet engraftments [16].…”
Section: Stemex® Copper Chelator Expansionmentioning
confidence: 90%
“…With this product, a fraction of a single UCB unit is expanded for 21 days with cytokines and TEPA, and infused in patients along with the unmanipulated cell fraction. Gamida Cell launched a multinational phase II/III registration trial (NCT00469729, http://clinicaltrials.gov website accessed on 3rd May, 2017) and concluded that transplanting a StemEx® graft improves a number of important clinical endpoints …”
Section: Clinical Applications Of Hspc – Ex Vivo Expanded Hspc In Hctmentioning
confidence: 99%
“…Fourteen phase I/II clinic trials [11,[14][15][16][17][18][19][20][21][22][23][24][25][26] and one phase II/III clinic trials [27] were included and their characteristics were presented in Table 1. One study [14] had a randomized control group while fourteen studies [11,[15][16][17][18][19][20][21][22][23][24][25][26][27] were single arm clinic trials for using historical controls. It's worth mentioning that the historical controls were well matched for transplantation conditioning, disease status, age, graft size, HLA matching and performance score criteria.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Children and adult patients were both included in eight studies [11, 15-17, 21, 24, 26, 27] while six studies [18-20, 22, 23, 25] only focused on adult patients. Twelve studies [11,15,17,18,[20][21][22][23][24][25][26][27] used myeloablative conditioning whereas only one study [19] used nonmyeloablative regimens, and two [14,16] used both of them. One manipulated UCB unit and one unmanipulated unit were co-infused to patients in eleven studies [14,[16][17][18][19][20][21][22][23][24][25].…”
Section: Study Characteristicsmentioning
confidence: 99%